Ultralong wavelength operation of a tunable multiwavelength Brillouin-Raman fiber laser in 1.65 μm band - Al-Alimi, Abdulmoghni Ali Wazea; Cholan, Noran Azizan; Shee, Yu Gang; Alresheedi, Mohammed Thamer; Goh, Chee Seong; Mahdi, Mohd Adzir (Elsevier BV, 2022)
A tunable multiwavelength Brillouin-Raman fiber laser (MW-BRFL) operated at an ultralong wavelength band (U-band) is presented in this work. The MW-BRFL was configured in a full-open linear cavity consisting of 11.2 km long dispersion compensating fiber that functioned as a Brillouin frequency shifter and Raman amplification gain medium. At Raman and Brillouin pump powers of 930 mW and 11.8 dBm, respectively, a stable multiwavelength generation with wavelength spacing of 0.17 nm was generated over a wavelength span of 53 nm. The generated channels covered a spectral range of 1630–1683 nm corresponding to 314 channels. The channels could also be tuned over 10 nm with an average optical signal-to-noise ratio greater than 26 dB. The laser system exhibited power fluctuation of less than 0.25 dB over 3 h. In a nutshell, the proposed MW-BRFL is promising with respect to its performance, simplicity and flexibility.